pH-responsive glycol chitosan-cross-linked carboxymethyl-β-cyclodextrin nanoparticles for controlled release of anticancer drugs - Wang Y (Dove Medical Press, 2015)
Yiwen Wang,* Fei Qin,* Haina Tan, Yan Zhang, Miao Jiang, Mei Lu, Xin Yao School of Chemistry and Chemical Engineering, University of Chinese Academy of Sciences, Beijing, People’s Republic of China *These authors contributed equally to this work Abstract: Carboxymethyl-β-cyclodextrin (CMβ-CD)-modified glycol chitosan (GCS) nanoparticles (GCS-CMβ-CD NPs) were synthesized, and their pH-sensitive drug-release properties were investigated. GCS-CMβ-CD NPs could encapsulate doxorubicin hydrochloride (DOX), and the encapsulation efficiency and loading capacity increased with the amount of CMβ-CD. Drug-release studies indicate that DOX released was greater in acidic medium (pH 5.0) than in weakly basic medium (pH 7.4). The mechanism underlying the pH-sensitive properties of the carrier was analyzed. Finally, the MCF-7 (human breast cancer) and SW480 cell lines (human colon cancer) were used to evaluate the cytotoxicity of the NPs. The drug-loaded carriers show good inhibition of the growth of cancer cells compared with free DOX, and the carriers have good biocompatibility. In addition, the drug-loaded NPs have sustained drug-release properties. All these properties of the newly synthesized GCS-CMβ-CD NPs suggest a promising potential as an effective anticancer drug-delivery system for controlled drug release. Keywords: MCF-7, SW480, surface plasmon resonance, encapsulation efficiency, loading capacity, cell viability